- 1-800-665-6601
- info@tutorpace.com

For example suppose 2 is multiplied 6 times which means 2 * 2 * 2 * 2 * 2 *2 or we can simply represent this as 2^6 which is equal to 64.

1) 6^2 + 5^3

2) x^3 + 2x^2 + x

3) (x^2 + 5x + 6) + (3x^2 + 2) + x^3 (1 + x)

4) (x+3)^3 + (x-2)^2

1) 6^2 + 5^3 = 36 + 125 =161

2) x^3 + 2x^2 + x = x(x^2 + 2x + 1)

= x (x + 1)^2

3) (x^2 + 5x + 6) + (3x^2 + 2) + x^3 (1 + x)

=x^2 +5x + 6 + 3x^2 + 2 + x^3 + x^4

=x^4 + x^3 + (x^2 + 3x^2) +5x + (6 + 2)

= x^4 + x^3 + 4x^2 + 5x + 8

4) (x+3)^3 + (x-2)^3

=x^3 + 3* x^2 * 3 + 3 * x * 3^2 + 3^3 + x^3 – 3 * x^2 * 2 + 3 * x * 2^2 -2^3

=x^3 + 9x^2 + 27x + 27+x^3-6x^2+12x-8

=2x^3 + 3x^2 + 39x+ 19